Discurso e história: representações do feminino em Ana Bolena - Cochete, Jéssica Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The central theme of this work is the construction of the identity of the female gender in the light of discourse analysis. To achieve this goal we used three different media productions made during the twentieth and twenty-first century that address the same historical character: Anne Boleyn, the second wife of Henry VIII. From the research and analysis of images carefully selected to represent three different real moments of Anne Boleyn, it was possible to realize how the same scene may have different approaches and how such approaches are influenced not only by the author of the work, but also by a discursive game that coordinates what can or can't be said by a society. The study concludes that the discourse analysis, besides assisting in the understanding of life and speeches of the historical character in question, also provides subsidies to know the society not only at the time that Anne Boleyn lived, but also at the time when the media productions studied here were performed

O tema central deste trabalho é a construção da identidade do feminino à luz da Análise do discurso. Para alcançar tal objetivo foram utilizadas três diferentes produções midiáticas feitas durante o século XX e XXI que abordam a mesma personagem histórica: Ana Bolena, a segunda esposa de Henrique VIII. A partir da investigação e análise de cenas selecionadas para representar três diferentes momentos reais de Ana Bolena foi possível notar como a mesma cena pode ter diferentes abordagens e como tais abordagens são influenciadas não só pelo autor da obra, mas também por um jogo discursivo que coordena o que se pode ou não ser dito por uma sociedade. O estudo conclui que a Análise do Discurso, além de auxiliar na compreensão da vida e dos discursos da personagem histórica em questão, também nos proporciona subsídios para conhecer a sociedade não só da época em que Ana Bolena viveu, mas também da época em que foram realizadas as produções midiáticas por este trabalho estudadas
Keywords: Ana Bolena Rainha, consorte de Henrique VIII, Rei da Inglaterra 1507-1536; Análise do discurso; Representações sociais; Identidade; Identity